Stability of shock waves in the modified quintic complex Ginzburg-Landau equation (Neliniini Kolyvannya, 2007)
We consider the shock type wave solution of the modified quintic complex Ginzburg Landau equation and make a numerical study of its spatiotemporal stability. Discussions related to the behaviour of this front wave are introduced and it is shown how the velocities of the wave could be utilized to collect information concerning the patterns formation in the system.